Medical Treatment for Pyometra in Cat - Palupi, Tantri Dyah Whidi; Suprayogi, Tri Wahyu; Ismudiono, Ismudiono (Universitas Airlangga, 2022)
The Pyometra case is a case that is often found in Female Cat. This case report will discuss the handling of a case of pyometra in a 7-year-old mixed breed cat who is being treated at Harmoni Pet Care, Menanggal, Gayungan, Surabaya, Indonesia. Reports from the owner that these cats are still in good appetite but sanguino-purulent discharge from the vagina was found. In clinically diagnosed with a pyometra, the treatment used to treat pyometra case was ovariohysterectomy. Postoperative care was carried out by administering antibiotics (Clanexi; Amoxicillin-Clavulanic Acid, 1 cc/kg, IM) given twice a day for 14 days, with the first 3 days being treated in the Harmoni Pet Care inpatient room and the 4th day to the 14th day of care is done at the owner's house, local antiseptic dressing at the incision site is continued for up to 14 days until the sutures in the skin sutures were absorbed by the cat's body.